1999
DOI: 10.1111/j.1469-7793.1999.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Na+‐H+ exchange impairs receptor‐mediated albumin endocytosis in renal proximal tubule‐derived epithelial cells from opossum

Abstract: Receptor‐mediated endocytosis is an important mechanism for transport of macromolecules and regulation of cell‐surface receptor expression. In renal proximal tubules, receptor‐mediated endocytosis mediates the reabsorption of filtered albumin. Acidification of the endocytic compartments is essential because it interferes with ligand‐receptor dissociation, vesicle trafficking, fusion events and coat formation. Here we show that the activity of Na+‐H+ exchanger isoform 3 (NHE3) is important for proper receptor‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
107
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 48 publications
(132 reference statements)
9
107
0
Order By: Relevance
“…While degradative pathways exist in most cell types, kidney proximal tubule cells have a particularly extensive apical endocytotic apparatus that is involved in the reabsorption and degradation of filtered proteins, and is also part of the extensive recycling of many critical apical plasma membrane proteins (Christensen, 1982;Christensen and Birn, 2002;Marshansky et al, 2002). Disruption of the V-ATPasemediated vesicle acidification process in proximal tubule cells using a variety of inhibitors, including bafilomycin, FCCP and NH 4 Cl, as well as Na + /H + exchanger 3 (NHE3) inhibition (Gekle et al, 1999), leads to diminished reabsorption of albumin (Marshansky et al, 2002) and other proteins, such as IgG light chains (Batuman and Guan, 1997) (Fig. 8).…”
Section: Brown and Othersmentioning
confidence: 99%
“…While degradative pathways exist in most cell types, kidney proximal tubule cells have a particularly extensive apical endocytotic apparatus that is involved in the reabsorption and degradation of filtered proteins, and is also part of the extensive recycling of many critical apical plasma membrane proteins (Christensen, 1982;Christensen and Birn, 2002;Marshansky et al, 2002). Disruption of the V-ATPasemediated vesicle acidification process in proximal tubule cells using a variety of inhibitors, including bafilomycin, FCCP and NH 4 Cl, as well as Na + /H + exchanger 3 (NHE3) inhibition (Gekle et al, 1999), leads to diminished reabsorption of albumin (Marshansky et al, 2002) and other proteins, such as IgG light chains (Batuman and Guan, 1997) (Fig. 8).…”
Section: Brown and Othersmentioning
confidence: 99%
“…Perhaps the main implications are in another direction: linkage to fibrosis and inflammation in some nephrotic diseases. Previous studies have linked increased albumin endocytosis (protein overloading) in the proximal tubule and NHE3 (13); inhibition of NHE3 in vitro decreases albumin endocytosis (13), and NHE3-dependent albumin endocytosis is partially linked to activation of nuclear factor-B (NF-B) (14). Therefore, activation of NHE3 by albumin may be related to the renal inflammation and fibrosis, which has been postulated to lead to both progression of renal disease and salt retention (15,16).…”
mentioning
confidence: 99%
“…Using immortalized kidney cell lines, others have shown that NHE3, which is abundantly expressed in and localized to endosomes in the cytoplasm and in the juxtanuclear compartment, functions at these sites in part to acidify endosomes and to facilitate vesicular fusion [22,23]. Moreover, it has been proposed that the trafficking of NHE3 to/from the cell membrane and the juxtanuclear compartment [24] represents a physiologic mechanism by which NHE3 controls Na + /H + exchange in epithelial cells of the kidney, colon, small intestine and gallbladder [25,26].…”
Section: Discussionmentioning
confidence: 99%